PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT EXODO ECOMMERCE INNOVASIA JAKARTA PUSAT - Delviani; Shella Puspita Sari (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to find out the influence of leadership style and organizational culture on employee performance at PT Exodo Ecommerce Innovasia. The method used is a quantitative method. The sampling technique used saturated sampling, totaling 80 respondents. The results of this research are, Leadership Style (X1) influences employee performance (Y) with the regression equation Y = 18.398 + 0.564 The hypothesis test obtained a value (Tcount 8.623 > Ttable 1.991), and a significance value of (0.000 <0.05), so Ho1 was rejected and Ha1 was accepted. This means that there is a significant influence of leadership style (X1) on employee performance (Y) on the performance of PT Exodo Ecommerce Innovasia employees. Organizational culture (X2) influences employee performance (Y) with the regression equation Y = 10.239 + 0.747 The hypothesis test obtained a value (Tcount 12.423 > Ttable value 1.991), and a significance value of (0.000 < 0.05), so Ho2 was rejected and Ha2 was accepted. This means that there is a significant influence of organizational culture (X2) on employee performance (Y) on the performance of PT Exodo Ecommerce Innovasia employees. Leadership Style (X1) and Organizational Culture (X2) influence employee performance (Y) with the regression equation Y = 8.060 + 0.227 Hypothesis test Fcount value 93.878 > Ftable 3.115. This proves that Ho3 is rejected and Ha3 is accepted. This means that there is a significant influence of leadership style and organizational culture on the performance of PT Exodo Ecommerce Innovasia Central Jakarta employees.